Formulation of patchouli oil spray gel (Pogostemon cablin Benth) and irritation test in rabbit - Junvidya Heroweti; M. Fatchur Rochman; Nurlaeli Fitriani; Safira Dinda (Pharmaciana, 2023)
Patchouli plant (Pogostemon cablin Benth) is one of the essential oil-producing plants widely used in perfume, cosmetic, aromatherapy, antiseptic, antibacterial, and antifungal industries. The essential oil derived from patchouli leaves contains terpenoid compounds with antibacterial and antifungal activity. This study aims to determine the optimum formulation of patchouli oil spray gel as a wound antiseptic and to observe the irritation test of the samples. The spray gel formulations of patchouli oil were prepared in various concentrations i.e. 5%, 7.5%, and 10% (v/v), solved in aqua dest with the addition of carbopol 940 as the gelating agent. The spray gels were tested to determine their physical characteristics, including the organoleptic test, homogeneity test, pH, adhesive dispersion test, viscosity test, and spray pattern test. The results showed that the patchouli oil spray gels were yellowish-white and had a distinctive odor and homogeneous texture with a pH 5. They all had adhesive dispersion, and the optimum viscosity of the spray gel was found at a 7.5% (v/v) concentration of patchouli oil. The irritation test was carried out using the patch test method with a score of erythema and edema. The results showed that all three formulas very mild irritation.